A rare cause of secondary organising pneumonia. Issue 3 (5th March 2021) - Fernandes, Ana Luisa; Ferro, Ana; Santos, Joana dos; Seabra, Bárbara
Abstract : Non-tuberculous mycobacterial pulmonary disease may have different clinical manifestations. We report a case of a 64-year-old woman presenting with persistent respiratory complaints, fever and radiological findings. Initially, she was diagnosed with community-acquired pneumonia, but after being submitted to an extensive investigation, including CT-guided transthoracic lung biopsy, a diagnosis of organising pneumonia (OP) was established. The patient was treated with corticosteroids with no favourable response. Subsequently, Mycobacterium avium complex (MAC) was identified in bronchoalveolar lavage culture. The patient was diagnosed with OP secondary to MAC infection and specific antibiotic treatment was initiated. This case represents an infrequent association and illustrates how important it is to investigate primary causes of OP to obtain a satisfactory treatment response.